Turning marine microplastics into components for producing innovative bituminous mastics: Boosting sustainability in road pavements - Yanqi Wang; Rosa Veropalumbo; Federica Recupido; Cristina Oreto; Quansheng Sun; Letizia Verdolotti; Assunta Campanile; Barbara Liguori; Nunzio Viscione; Gianluca Dell’Acqua; Francesca Russo; Giuseppe Cesare Lama (Results in Engineering)
Marine-microplastics pose a significant environmental threat due to their accumulation, which causes irreversible damage to marine ecosystems and wildlife. However, these same microplastics can be repurposed to enhance the performance of asphalt mastics, improving road durability and promoting recycling. This study investigates the feasibility of using marine-microplastics as modifiers in two types of bituminous mastics, at a concentration of 6wt %. These include the conventional black neat bitumen (for road pavements) and a more sustainable, transparent Albino bitumen (for pedestrian pavements). The modified mastics are characterized by a range of physical-rheological, chemical, morphological, and thermal properties. The potential for plastic leaching is evaluated by simulating acid rain conditions (pH≤5.6). Additionally, a Life-Cycle-Assessment methodology is applied to quantify the Climate Change indicator for 1m² of road pavement using the obtained mastics. Results show that incorporating marine-microplastics improves the mechanical and rheological properties of bituminous mastics; in fact, this latter shows a softening point improvement of 9.8 °C compared to the neat bitumen (46 °C) and at the same time the addition of marine-microplastics into neat bitumen produces a stiffness reinforcement by over 80 % compared to the conventional mastic. Furthermore, leachate heavy metal concentrations decrease by up to 85 %, for Cd, which reduces from 14 mg/kg (neat bitumen) to 2mg/kg, by employing marine- microplastics. Notably, the climate change indicator is reduced by up to 16 % compared to traditional solutions, attributed to the extended service life provided by marine-microplastics in the mastics. This study presents a promising recycling strategy, offering a sustainable solution for road engineering applications.